Museu da Universidade Federal do Pará: a interação do museu com o público escolar através da mediação cultural - RODRIGUES, Mayra do Socorro de Araújo (2019)
This study analyzes the relationship the high school school public sets with the Museum of the Federal University of Pará (MUFPA) at the time of the visit, in which the student comes into contact with its exhibits and will be guided by a cultural mediator. From these assumptions, methodological procedures referring to a literature review based on the precepts of Santos (2008), Marandino (2008), Cury (2005), among others, were used, in addition to fieldwork which enabled the observation, research and the closest contact with the visiting public in analysis. In this sense, we tried to understand the museum from the New Museology principles, which comprise it as a relational and educational space, seeking to build a relevant socio-cultural role in society and in which the public response shall be considered fundamentally important for the development of their practices. For this research the Cultural Mediation in museums is considered the object of study because it has great relevance within the museological space, for making possible a closer contact between the museum and its public, serving as a stimulating factor for visitors pass to visit its spaces more frequently.